MECHANISM OF DATA COLLECTION ON CAPTURE FISHERIES PRODUCTION AT FISHERIES OFFICE MERAUKE REGENCY - Rumbino, Viceriani Siampa; Satumalay, Victor IJ; Kuara, Antoneta; Mappasessu, Baso (Jurnal Penelitian Perikanan Laut (Albacore), 2025)
Merauke Regency Fisheries Office has a strategic role in the management of capture fisheries resources through the mechanism of fisheries production data collection. Accurate and systematic data collection is very important to support sustainable fisheries management policies, especially in implementing the Measured Fishing (PIT) policy in accordance with PP No. 11 of 2023. This study aims to determine the capture fisheries production data collection mechanism implemented by the Merauke Regency Fisheries Office. This research was conducted March to June 2024 at the Fisheries Service of Merauke Regency. The data collection method was carried out by interview method and field observation. Based on the results of the research, it was found that the capture fisheries production data collection mechanism at the Merauke Regency Fisheries Service consists of three main stages, namely data collection, data processing, and reporting. The data collection process is carried out through three sources, such as monthly reports of fish landed at the Perikanan Nusantara Port (PPN), production data from the Joint Business Group (KUB), and Fish Origin Certificate (SKAI). The amount of capture fisheries production of the Merauke Regency fisheries service in 2023 was 14,504,697 kg with details; the amount of fish landed at the archipelago fishing port (PPN) was 6,752,813 kg, in the Joint Business Group (KUB) was 6,664,724 kg and the fish certificate of origin (SKAI) was 1,087,160 kg. Key words: data collection mechanism, Merauke, production,capture fisheries